Implikasi Kepala Rumah Tangga Tidak Mampu Memberi Nafkah Dalam Mewujudkan Keutuhan Rumah Tangga Perspektif Maqashid Syari’ah - Netti, Misra; Nur, Syamsiah; Setiawan, Thoat (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This research examines the effect of the inability of the head of the family to fulfill the responsibility of providing for his family from the point of view of Maqashid Shari'ah. The husband's obligation to provide for his wife and children has been explained in the Qur'an and strengthened through legislation, such as Law No. 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI). This research aims to understand the impact of the husband's inability to fulfill his obligation to provide for the stability of the household and identify solutions that can be done by the wife to maintain family harmony according to the principles of Maqashid Shari'ah. A normative qualitative approach is used in this research by analyzing the content of relevant secondary data. The results show that the husband's failure to fulfill his livelihood can be caused by various factors, such as economic conditions, unemployment, or physical limitations, which have the potential to threaten the integrity of the family. However, the role of a working wife can be one of the efforts to support the family's needs, as long as she maintains her role as a wife and mother in the family.